INFLUENCE OF SCHOOL PRINCIPAL LEADERSHIP AND WORK DISCIPLINE TOWARDS TEACHER PERFORMANCE - Amiruddin Siahaan; Yusuf Hadi Jaya; Rahmadiah Siregar (Universitas Islam Negeri (UIN) Sumatera Utara, 2019)
The data analysistechniques used in description analysis include correlation analysis and regression. The resultsshowed that the school principal's leadership style influenced the teacher's performance by44.5%.These findings give the meaning that 44.5% of teacher performance can be predicted throughthe principal's leadership style. The work discipline affects the teacher's performance by 53.4%. Thesefindings give meaning 31.60% of the teacher's performance can be predicted through work discipline.The leadership style of the school principal and work discipline jointly affects the teacher'sperformance by 63.9% while the remaining 36.1% is derived from the other variables outside of this study.